The Bio-Rights Scheme in The Use of The Sun as a Renewable New Energy Promotes The Availability of Sustainable Electricity Energy Sources - Yuniar, Riska Sasi; Najicha, Fatma Ulfatun (Universitas Negeri Semarang, 2024)
Sunlight is an energy that has great potential to support the availability of sustainable power sources. Often in the construction of EBT facilities, the community is hampered by expensive project costs. The study aims to examine the policies that have been drafted by the government regarding the exploitation of solar energy potential in Indonesia, the Regulations and Legislation that form the basis of energy management, as well as to offer alternative solutions related to how the energy management ecosystem scheme is appropriate so that it can respond to the problems of the construction of the EBT project. In the Bio-Rights scheme, indigenous and local communities have an important role to play in the use of solar heat. They have the right to participate in decision-making, benefit from solar heat, and protect natural resources.